Developing the Natural Potential of Langgahan Village as an Ecotourism-based Tourist Village - I Wayan Pardi; Ketut Bayu Ananta Krisna; Kadek Bintang Sri Kusuma Rahayu; Luh Dita Apriladiwangi Pramesti; Putu Mayong Satya Ardhita; Made Dwi Semara Guna (Universitas Pendidikan Ganesha, 2026)
Langgahan Village has great potential for the development of ecotourism-based tourism. Natural beauty such as Pelisan Waterfall, fertile agricultural land, and rich local culture are important assets for making this village a sustainable tourist destination. This paper aims to identify natural resource potential, assess existing challenges and opportunities, and formulate development strategies using a participatory approach involving the community. The approach used involves field studies, interviews, and documentation. Although the ecotourism sector offers promising opportunities, there are still obstacles such as limited infrastructure, insufficient promotion, and inadequate empowerment of the local community. Development efforts can be carried out through enhancing human resource capacity, community-based management, and utilizing digital technology as a promotional tool. With these strategies, Langgahan Village is expected to have the potential to become a model for outstanding and sustainable ecotourism village development.